2022
DOI: 10.3390/cancers14153803
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Colorectal Cancer Surgery: Present and Future Perspectives

Abstract: Artificial intelligence (AI) and computer vision (CV) are beginning to impact medicine. While evidence on the clinical value of AI-based solutions for the screening and staging of colorectal cancer (CRC) is mounting, CV and AI applications to enhance the surgical treatment of CRC are still in their early stage. This manuscript introduces key AI concepts to a surgical audience, illustrates fundamental steps to develop CV for surgical applications, and provides a comprehensive overview on the state-of-the-art of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The results of this study also revealed that AI has important applications in disease screening. AI can have a major role in the screening process, by supporting the screening process and staging, as categorized as the third theme entitled "screening" (43)(44)(45)(46)(47)(48). Screening is an important stage in decision making for disease management and future stages of intervention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also revealed that AI has important applications in disease screening. AI can have a major role in the screening process, by supporting the screening process and staging, as categorized as the third theme entitled "screening" (43)(44)(45)(46)(47)(48). Screening is an important stage in decision making for disease management and future stages of intervention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple institutions must collaborate in this context to ensure that data are diverse and representative ( 46 ). Such datasets will be critical for training stronger AI models, and also for demonstrating generalizability through external validation studies ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of minimally invasive surgery, the application of AI in the field of surgery has also been gradually valued. Compared with more complicated CRC surgery, AI was applied earlier in lung cancer and breast cancer surgery ( 138 ). Notably, people have begun to study the application of AI in colorectal surgery, and gradually realize that AI can provide a new direction for the development of colorectal surgery.…”
Section: The Application Of Ai In Crc Treatmentmentioning
confidence: 99%
“…Much research data on CRC is pouring out. Computer vision (CV) is a subfield of AI that can be used to analyze and evaluate video data ( 138 ). Some researchers in Japan have collected and analyzed 300 videos of laparoscopic colorectal surgery, hoping that these data sets may be employed to optimize the CNN performance in CV ( 118 ).…”
Section: The Application Of Ai In Crc Treatmentmentioning
confidence: 99%